Foreign experience and CEO compensation - Conyon, Martin J.; Haß, Lars Helge; Vergauwe, Skrålan; Zhang, Zhifang (Journal of Corporate Finance, 2019)
This paper investigates the relationship between a CEO's foreign experience and CEO compensation. Our analysis is based on the constituent firms of the UK FTSE 350 index from 1999 to 2015. We find that foreign CEOs and national CEOs with foreign working experience receive significantly higher levels of total compensation compared to similar UK CEOs without such characteristics. The results are robust to the endogenous CEO selection using propensity score matching methods, as well as other modelling approaches. Our results show that pay premiums are attributable to the specialized foreign expertise and foreign networks of CEOs, which stem from foreign experience rather than broader general managerial skills.